Residuos de fármacos anabolizantes en carnes destinadas al consumo humano - Álvaro Luis Fajardo-Zapata; Francy Janeth Mendez-Casallas; Luis Humberto Molina (Universitas Scientiarum)
Residues of anabolic drugs in meat intended for human consumption. The production of meat for human consumption is one of theimportant items in the economy of a country. This activity has great socio economic importance as it serves as a basis for development,employment generation and sustainability of a country. The demand for animal protein is one of the most precious and necessary factors tomaintain a proper biological development of human beings in active growth as well as being a source of growth and tissue regeneration.Consumption has increased because populations continue to grow and there is continuous migration to the cities, which makes the offerinsufficient, and therefore it is necessary to accelerate, introduce technology and improve the meat production process. Industry also seeksa reduction in production costs by producers in this sector of the economy, leading to the use and incorporation of technology and cuttingedgeknowledge to improve yield production of meat. Such knowledge comprises the scientific basis of the use of growth hormones andpromoters (anabolic steroids and others) to accelerate and increase the production of meat. Although there has been an increase inproduction, residual substances can remain in the meat intended for human consumption which can lead to changes in the health ofconsumers.